What's Stopping You from Migrating to Mobile Tourism Shopping?. Issue 6 (2nd November 2022) - Wan, Sze-Mun; Cham, Li-Na; Tan, Garry Wei-Han; Lo, Pei-San; Ooi, Keng-Boon; Chatterjee, Rajat-Subhra
ABSTRACT: Tourism shopping via mobile applications has revolutionized the tourism industry. The research examined the antecedents to the adoption of mobile tourism shopping (MTS) via an integrated model, consisting of the Mobile Technology Acceptance Model, consumer perception of merchant ethics, consumer decision-making styles, and characteristics of mobile applications. The results were empirically validated via the PLS-SEM-ANN method. The findings indicated that mobile usefulness, mobile ease of use, application quality, and service quality have significant positive correlations with the intention to use MTS, whereas privacy concern has displayed a significant negative relationship. Moreover, source reliability, application reputation, perfectionism, and novelty-fashion consciousness were revealed to be statistically insignificant to the development of adoption intention toward MTS. Furthermore, the ANN results have indicated the existence of a non-linear hidden attribute in the prediction of ANN Model A. The research has generated valuable theoretical implications and practical insights. For one, the advantages that come with the adoption of MTS and the security measures taken by the service providers should be highlighted to the prospects via effective marketing messages to nurture confidence, which can subsequently drive adoption.